The Determinants of Debt Maturity Structure for Chinese Listed Companies - LIN, WENYI (2020)
The funds from financing are necessary for companies to maintain their business activities in the process of operation and development. Debt financing is a crucial financing method, whose maturity choice is a key element of debt financing decisions. So determiners of debt maturity decision are research priorities, which regard Chinese listed companies as research subject in this article. First, the theories of debt maturity are reviewed, including agency cost theory, signaling and liquidity risks hypothesis, maturity matching principles, and tax theory. Then, variables are determined and hypotheses are proposed by combing these theories and previous research results. Third, data of 1,494 A-shares Chinese listed companies over 8 years between 2012 and 2019 are used as the full sample. And according to the firm scales which is based on the median company size, different periods which are from 2012 to 2015 and from 2016 to 2019, and ownership which are state-owned firms or non-state-owned firms, seven fixed effects models are established.